Kontekstualisasi dalam penyebaran Islam: analisis pola pembentukan Islam di Nusantara - Rumahuru, Yance Zadrak (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article analyzes the pattern of the spread of Islam in Nusantara, especially in Maluku islands. It aims to develop the thought of spread of Islam as proposed by Taufik Abdullah and Djoko Suryo. It is constructed based on the writer’s research findings in Ternate and Tidore North Maluku, also in Ambon island and Haruku island, Central Maluku. Besides field data, literature study on the spread of Islam in Indonesia and Southeast Asia is used as well. Referring to the macro context proposed by Taufik Abdullah and Djoko Suryo, the writer examines the micro context of Maluku islands, and it is found that: First, the spread of Islam in Maluku takes place through a contextualization pattern. Second, the presence of Islam in Maluku islands is a momentum for the development of society in the past and influenced the existence of Islam until now. Through Islam, the local communities are able to realize the outside world and build a wider communication that allows them to experienced modernization. Furthermore, this article can be placed as part of the historical and religious identity studies undertaken to assert the existence of Islam that has contributed to build the civilization of society, either in Maluku or in Indonesia and Southeast Asia.